The Influence of Work Facilities, Teacher Teaching Discipline, and Work Motivation on Teacher Performance at Madrasah Aliyah State (MAN) Dairi - Syasmita, Ria; Bambang, Bambang; Taufik, Muhammad; Erwin, Erwin; Helmi, Tengku Ahmad; Rahayu, Sri (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This exploration examines the impact of work offices, instructors showing discipline and work inspiration on educator execution at Madrasah Aliyah Negeri (MAN) Dairi. This examination intends to analyze the impact of work offices, educators showing discipline and work inspiration both somewhat and at the same time on instructor execution at Madrasah Aliyah Negeri (MAN) Dairi. This exploration is a quantitative examination, and the inspection procedure utilized is absolute testing. The example was 50 educators. The consequences of the exploration show that the work offices variable has a t-count of 4.941 and a meaning of 0.000, the educator showing discipline variable has a t-count of 4.325 and a meaning of 0.000, and work inspiration has a t-count of 3.890 and a meaning of 0.000. In this way, one might say that, to some extent, every one of the factors of work offices—educators showing discipline and work inspiration—significantly affects educator execution. At the same time, work offices, instructors showing discipline and work inspiration likewise meaningfully affect educator execution at Madrasah Aliyah Negeri (MAN) Dairi with a F worth of 47.977 and a meaning of 0.000.